Endothelin-1 (ET-1) stimulates carboxy terminal Smad2 phosphorylation in vascular endothelial cells by a mechanism dependent on ET receptors and de novo protein synthesis. (1st December 2016) - Sharifat, Narges; Mohammad Zadeh, Ghorban; Ghaffari, Mohammad-Ali; Dayati, Parisa; Kamato, Danielle; Little, Peter J; Babaahmadi-Rezaei, Hossein
Abstract: Objective: G protein-coupled receptor (GPCR) agonists through their receptors can transactivate protein tyrosine kinase receptors such as epidermal growth factor receptor and serine/threonine kinase receptors most notably transforming growth factor (TGF)-β receptor (TβRI). This signalling mechanism represents a major expansion in the cellular outcomes attributable to GPCR signalling. This study addressed the role and mechanisms involved in GPCR agonist, endothelin-1 (ET-1)-mediated transactivation of the TβRI in bovine aortic endothelial cells (BAECs). Method: The in-vitro model used BAECs. Signalling intermediate phospho-Smad2 in the carboxy terminal was detected and quantified by Western blotting. Key finding: ET-1 treatment of BAECs resulted in a time and concentration-dependent increase in pSmad2C. Peak phosphorylation was evident with 100 nm treatment of ET-1 at 4–6 h. TβRI antagonist, SB431542 inhibited ET-1-mediated pSmad2C. In the presence of bosentan, a mixed ETA and ETB receptor antagonist ET-1-mediated pSmad2C levels were inhibited. The ET-mediated pSmad2C was blocked by the protein synthesis inhibitor, cycloheximide. Conclusion: In BAECs, ET-1 via the ETB receptor is involved in transactivation of the TβRI. The transactivation-dependent response is dependent upon de novo protein synthesis.